2018
DOI: 10.1002/jez.b.22806
|View full text |Cite
|
Sign up to set email alerts
|

Heterochronic opsin expression due to early light deprivation results in drastically shifted visual sensitivity in a cichlid fish: Possible role of thyroid hormone signaling

Abstract: During early ontogeny, visual opsin gene expression in cichlids is influenced by prevailing light regimen. Red light, for example, leads to an early switch from the expression of short-wavelength sensitive to long-wavelength sensitive opsins. Here, we address the influence of light deprivation on opsin expression. Individuals reared in constant darkness during the first 14 days post-hatching (dph) showed a general developmental delay compared with fish reared under a 12:12 hr light-dark cycle (control group). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 104 publications
3
35
0
Order By: Relevance
“…Escobar‐Camacho et al (2016) found that the same three opsins were expressed in all of three different studied Amazonian cichlids, suggesting that Amazonian cichlids generally have a limited opsin repertoire. Although sampled representatives of Central American lineages expressed the same three cone opsins in our study, they appear to be generally less constrained in their visual repertoire as recent studies found more visual diversity among them, with at least some of them also expressing sws1 , sws2b and rh2b in certain habitat types or developmental stages (Härer, Meyer, & Torres‐Dowdall, 2018; Karagic, Härer, Meyer, & Torres‐Dowdall, 2018).…”
Section: Discussionsupporting
confidence: 46%
“…Escobar‐Camacho et al (2016) found that the same three opsins were expressed in all of three different studied Amazonian cichlids, suggesting that Amazonian cichlids generally have a limited opsin repertoire. Although sampled representatives of Central American lineages expressed the same three cone opsins in our study, they appear to be generally less constrained in their visual repertoire as recent studies found more visual diversity among them, with at least some of them also expressing sws1 , sws2b and rh2b in certain habitat types or developmental stages (Härer, Meyer, & Torres‐Dowdall, 2018; Karagic, Härer, Meyer, & Torres‐Dowdall, 2018).…”
Section: Discussionsupporting
confidence: 46%
“…Melatonin is involved in the regulation of growth and development, and minimal light thresholds are needed for proper larval development in most fishes [18]. Indeed, dark-raised A. citrinellus have a disrupted thyroid metabolism [13], a downstream target of melatonin [18]. Not surprisingly, surgical removal of the pineal gland has been reported to cause spinal deformities in vertebrates [23].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory-reared Midas cichlids originated from a mixed-sex stock tank comprising wild-caught individuals collected in Lake Nicaragua in 2010 and 2013. For the experiment, conducted in 2017, embryos from an A. citrinellus brood were divided into 12 groups 2 days post-fertilization (n ¼ 10 each); six were placed in a 12 L : 12 D cycle and six in constant darkness (for details, see [13]). Two weeks after hatching, the percentages of surviving fish and of those with spinal deformities were quantified.…”
Section: Materials and Methods (A) Mortality And Spinal Deformities Inmentioning
confidence: 99%
“…Expression levels of opsin genes were based on qPCR data of two technical replicates and mean threshold cycle (Ct) values were used for subsequent analysis. Before and after the 14-day experimental period, expression of cone opsins was calculated proportionally to overall cone opsin expression (incorporating qPCR efficiencies) as previously described [4,14]. For fish reared under either blue or red light for 118 and 132 days, we tested whether treatment or age has an effect on cone opsin expression by using a nonparametric equivalent to a two-way ANOVA, the Scheirer–Ray–Hare test [17].…”
Section: Methodsmentioning
confidence: 99%
“…During ontogeny, many cichlid species shift opsin expression from short- to long-wavelength sensitivity [10]. Phenotypic plasticity in opsin expression seems to be rather common during this ontogenetic progression but appears to be restricted once the adult visual phenotype has been reached [5,14], but see [6,15]. Amphilophus astorquii , our study species, shows a paedomorphic visual phenotype, which might allow this species to maintain some degree of plasticity into adulthood, at least in the same direction as the ontogenetic progression (towards longer wavelengths) [4].…”
Section: Introductionmentioning
confidence: 99%